Developing e-laboratory instructions based on the unity of sciences paradigm in producing tempeh - Dian Fadlilati; Saifullah Hidayat; Hafidha Asni Akmalia (Universitas Muhammadiyah Malang, 2023)
Hands-on activities experienced many obstacles during the Covid-19 pandemic. So, students' skills in the laboratory were also affected. In addition, the inculcation of Islamic values in learning needs more attention in religion-based schools. The study aimed to develop a design of e-laboratory instruction based on the unity of sciences paradigm on biotechnology material (producing tempeh) and prove its feasibility. This study uses the ADDIE model by Dick and Carey (1996). The data collection techniques are interviews, questionnaires, and documentation. The subjects of this study were students of twelfth graders in science class in SMA Hasyim Asy'ari Pekalongan, Central Java. The validation results from material and media experts show that e-laboratory instruction is very eligible, 91.81% and 85.38%. While the integration expert validators state that design is very high (86.67%). The biology teacher's response reached 85.71% (very high). The result of the pilot test is 85.41%, categorized as very high. The e-laboratory instruction based on the unity of sciences paradigm in producing tempeh is suitable for learning.